Selective intracellular delivery of perfluorocarbon nanodroplets for cytotoxicity threshold reduction on ultrasound‐induced vaporization - Ishijima, Ayumu (Cancer Rep (Hoboken), 2019)
BACKGROUND: Phase‐change nanodroplets (PCNDs), which are liquid perfluorocarbon nanoparticles, have garnered much attention as ultrasound‐responsive nanomedicines. The vaporization phenomenon has been employed to treat tumors mechanically. However, the ultrasound pressure applied to induce vaporization must be low to avoid damage to nontarget tissues. AIMS: Here, we report that the pressure threshold for vaporization to induce cytotoxicity can be significantly reduced by selective intracellular delivery of PCNDs into targeted tumors. METHODS AND RESULTS: In vitro experiments revealed that selective intracellular delivery of PCNDs induced PCND aggregation specifically inside the targeted cells. This close‐packed configuration decreased the pressure threshold for vaporization to induce cytotoxicity. Moreover, following ultrasound exposure, significant decrease was observed in the viability of cells that incorporated PCNDs (35%) but not in the viability of cells that did not incorporate PCNDs (88%). CONCLUSIONS: Intracellular delivery of PCNDs reduced ultrasound pressure applied for vaporization to induce cytotoxicity. Confocal laser scanning microscopy and flow cytometry revealed that prolonged PCND‐cell incubation increased PCND uptake and aggregation. This aggregation effect might have contributed to the cytotoxicity threshold reduction effect.